2009
DOI: 10.1159/000226612
|View full text |Cite
|
Sign up to set email alerts
|

Orphan Nuclear Receptor Rev-erb Alpha Gene <i>(NR1D1)</i> and Fluvoxamine Response in Major Depressive Disorder in the Japanese Population

Abstract: Background: Sleep-wake disturbance, frequently observed in major depressive disorder (MDD), negatively influences clinical status. Treatment with antidepressants also reportedly affects circadian rhythms. In a recent in vitro study, the nuclear receptor Rev-erbα was reported to be related to circadian rhythms, and was shown to be involved in the biological action of lithium therapy. Therefore, we examined the association between the orphan nuclear receptor Rev-erbα gene (NR1D1) and the efficacy of fluvoxamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Two recent studies report nominal significant associations of genetic variation in NR1D1 in BD (Kishi et al, 2008;Severino et al, 2009) that are not replicated in our BD subset of patients, but conversely we found a positive nominal association in our MDD subsample, suggesting the possible involvement of NR1D1 in other MD-related phenotypes. However, NR1D1 gene does not seem to have a major role in the antidepressant response in MDD (Kishi et al, 2009c), despite its key role in circadian rhythm regulation. These findings deserve further investigation in larger samples considering homogeneous clinical phenotypes and circadian subphenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Two recent studies report nominal significant associations of genetic variation in NR1D1 in BD (Kishi et al, 2008;Severino et al, 2009) that are not replicated in our BD subset of patients, but conversely we found a positive nominal association in our MDD subsample, suggesting the possible involvement of NR1D1 in other MD-related phenotypes. However, NR1D1 gene does not seem to have a major role in the antidepressant response in MDD (Kishi et al, 2009c), despite its key role in circadian rhythm regulation. These findings deserve further investigation in larger samples considering homogeneous clinical phenotypes and circadian subphenotypes.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, we reported that NR1D1 was not associated with major depressive disorder and selective serotonin reuptake inhibitor response to major depressive disorder [7, 22]. On the other hand, we detected the associations between PROKR2 and not only mood disorders including major depressive disorder and bipolar disorder but also METH dependence and METH-induced psychosis in the Japanese population [12, 23].…”
Section: Discussionmentioning
confidence: 77%
“…The evidence for this relation is discussed in more detail in our previous papers and a review by Barnard and Nolan [4-7]. …”
Section: Introductionmentioning
confidence: 99%
“…A recent study has showed an association between common diseases such as schizophrenia and rare variants. If the genetic background of METH-induced psychosis is accurately described by the common disease-rare variants hypothesis, further investigation such as medical resequencing using larger samples will be required [8, 12-17]. …”
Section: Discussionmentioning
confidence: 99%